A Sonographic Enthesitic Index of lower limbs is a valuable tool in the assessment of ankylosing spondylitis. Issue 8 (7th December 2006) - Alcalde, M; Acebes, Juan C; Cruz, M; González-Hombrado, L; Herrero-Beaumont, G; Sánchez-Pernaute, O
Abstract : Background: Enthesitis is a remarkable feature of ankylosing spondylitis (AS) not specifically approached by the available measuring tools for the disease. Ultrasonography (US) has proved to be an excellent technique for the assessment of tendon pathology. Objective: To test a Sonographic Entheseal Index (SEI) of the lower limbs in a cohort of patients with AS, as a potential measuring tool. Methods: 44 patients with AS and 10 healthy controls were enrolled. Bath Ankylosing Spondylitis Functional Index and Bath Ankylosing Spondylitis Disease Activity Index, pain at entheseal points, severity of symptoms, acute-phase reactants, Schober's test and stage of sacroiliitis were recorded. Patients underwent US examination of five entheseal regions from both lower limbs by two experts. Hypoechogenicity, increased tendon thickness, peritendinous oedema and bursitis were considered signs of active inflammation. Insertional bone erosions, intratendinous calcifications, decreased thickness and tears were considered signs of chronic injury. Each alteration independently scored one point. Data were analysed with Spearman's correlation method. Results: A significant interobserver correlation in SEI scores (p<0.001) and a fine discriminative power between controls and patients were observed. Acute entheseal lesions predominated (63% vs 37%), the most frequent alteration being tendon hypoechogenicity (43%). 72% of all lesions were located at the foot. The SEI correlated with reduction of Schober's test (p<0.02), but not with other activity or severity parameters. Conclusions: A scoring method such as the SEI may be of help in characterising entheseal injury in AS, and for decision making in these patients.